RESTORATIVE JUSTICE POLICY TOWARDS PERPETRATORS OF TRAFFIC ACCIDENTS WITH DEATH - Shodiq, Ja'far; Nurahmawati, Dian; Isnaini, Enik (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
Traffic accidents are unpredictable in time, place and cause. Traffic accidents occur due to a lack of awareness of road users which then results in damage and even the safety of someone's life. Thus, a restorative justice approach emerged that focuses on the process of returning things to their original state by prioritizing a sense of peace between the perpetrator and the victim. The purpose of this study is to understand the application of restorative justice policies to the perpetrators of traffic violations with fatalities. The research uses normative juridical type of writing, with statute approach and concept approach. The legal materials used are primary legal materials including: The Book of Law. From this research it can be concluded: the legal basis governing the Implementation of Road Traffic and Transportation is Law Number 22 of 2009 and Government Regulation Number 30 of 2021. The restorative justice policy is regulated in the Regulation of the Indonesian National Police (PERKAPOLRI) Number 8 of 2021, the Prosecutor's Regulation (PERJA) Number 15 of 2020, and the Supreme Court Regulation Number 2 of 2012. Regulations regarding traffic offenders with fatalities have not been specifically regulated by law, so it needs to be a common concern in order to achieve fair law enforcement for traffic offenders with fatalities through a restorative justice approach.